The Analisis Kepastian Hukum terhadap Kontrak Elektronik dan Smart Contract - I Nyoman Wahyu Ariartha; I Made Sudharma; Putu Ulandari Sri Lestari (Fakultas Hukum, Universitas Warmadewa, 2025)
The rapid development of information technology has significantly transformed the field of contract law in Indonesia. Electronic contracts and smart contracts have emerged as new legal phenomena that require adaptation within the national legal framework. This article aims to analyze the legal certainty of online and smart contracts in Indonesia’s positive law, particularly in light of recent regulations such as Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 on Electronic Information and Transactions, and Law Number 27 of 2022 on Personal Data Protection. Using a normative juridical method with statutory and conceptual approaches, this study finds that electronic contracts are legally recognized but still face challenges in authentication, evidentiary standards, and legal protection. Meanwhile, smart contracts are not yet explicitly regulated, though they can be deemed valid under the principles of pacta sunt servanda and free will. The study concludes that a Digital Contract and Smart Contract Law is urgently needed to ensure that Indonesia’s legal system can balance technological efficiency with legal justice.